Multifaceted impacts of widespread renewable energy integration on socio-economic, ecological, and regional development - Anis ur Rehman; Sheeraz Iqbal; Aqib Shafiq; Nahar F. Alshammari; Saadat Hanif Dar; Raja Tahir Iqbal (Sustainable Futures)
Clean and sustainable energy has become a main objective in the modern world. However, achieving clean and sustainable energy required active participation from customers and widespread adoption of Renewable Energy Resources (RERs). Inadequate awareness about the economic benefits of RERs could result in reduced customer engagement and diminished interest from governments in promoting the installation of RERs. The paper proposes an exploration of the economic, environmental, and social benefits associated with the widespread integration of RERs in the power distribution network to effectively address the benefits of widespread RERs integration. It also highlights how this extensive integration of RERs has the potential to foster economic growth in the region and benefit consumers. In addition, the paper examines the power-sharing dynamics between the grid and RERs to analyze the reduction in grid burden, load and energy management, and conduct sensitivity analysis considering various customer responses for the installation of RERs. The paper presents a comprehensive case study that includes four districts within the region of East Kashmir. In the case study, revenue climbed to $103.6 million with a 70% surge in renewable energy use, drastically cutting carbon emissions to 285.8 million kg/year and energy costs to $0.10/kWh. Moreover, energy self-sufficiency was highlighted by a 47% renewable penetration and 110 million kWh sold at 70% customer engagement.